Digesting Femininities : The Feminist Politics of Contemporary Food Culture - Jovanovski, Natalie (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This volume addresses how the rhetoric of feminist empowerment has been combined with mainstream representations of food, thus creating a cultural consciousness around food and eating that is unmistakably pathological. Throughout, Natalie Jovanovski discusses key texts written by women, for women: best-selling diet books, popular cookbooks produced by female food celebrities, and iconic feminist self-help texts. This is the first book to engage in a feminist analysis of body-policing food trends that focus specifically on the use of feminist rhetoric as a harmful aspect of food culture. There is a smorgasbord of seemingly diverse gender roles for women to choose from, but many encourage breaking gender norms and embracing a love of food while perpetuating old narratives of guilt and restraint. Digesting Femininities problematizes the gendering of food and eating and challenges the reader to imagine what a genderless and emancipatory food culture would look like.